When Do Entrepreneurs Accurately Evaluate Venture Capital Firms’ Track Records? A Bounded Rationality Perspective - Hallen, Benjamin L.; Pahnke, Emily Cox (Academy of Management Journal, 2016)
There has been substantial research on the value of young firms engaging high-quality partners. This literature, as well as the broader firm reputation literature, has tended to assume that individuals leading such firms find it relatively easy to accurately assess potential partner quality as reflected in their track record of past performance and behavior. Yet this prior work has largely focused on information-rich environments where potential partners are generally large and receive substantial public attention, and with whom evaluators may have high familiarity. In contrast, we draw on bounded rationality to theorize about how in information-sparse environments, individuals may misperceive the quality indicated by a firm’s objective track record. We argue that accurate evaluations depend not only on individuals’ motivation and ability to access information but on the convergence of these factors with attributes of the potential partner being evaluated. We test and find support for our framework using a novel dataset of 1,278 ratings of the quality of 153 early-stage venture capital firms by entrepreneurs that approached these firms for investments. Overall, this paper extends understanding of firm reputation dynamics to information-sparse contexts, and explores why individuals such as entrepreneurs may at times have difficulty accurately evaluating partners.